Differences in Surgical Performance of Internal Limiting Membrane Peeling for Macular Hole Repair Between Supervised Vitreoretinal Fellows and Vitreoretinal Faculty at a Single Institution. (September 2017) - Gizicki, Robert; Chow, David; Mak, Michael Y.K.; Wong, David T.; Muni, Rajeev H.; Altomare, Filiberto; Berger, Alan R.; Giavedoni, Louis
Purpose: To investigate the differences in surgical maneuvers between vitreoretinal fellows and experienced vitreoretinal surgeons (attendings) when performing internal limiting membrane (ILM) peel during macular hole (MH) surgery and repair. Methods: Prospective case series. Macular hole surgeries performed by fellows and attendings at St Michael's Hospital (Toronto, Canada) were recorded during a 12-month period. Evaluation of recordings was masked. Total peel time (TPL) in seconds, total movement attempts initiating and extending ILM flaps, intrasurgical complications, and surgical efficiency (ratio of approaches leading to case progression to total approaches) were quantified. Results: A total of 145 surgeries were evaluated; 44 met inclusion and exclusion criteria. Of the 44 cases, 25 were performed by fellows and 19 by attendings. Mean TPL was shorter for attendings (336 vs 506 seconds, P = .0032). Attendings had a lower average total movement attempts (32.2 vs 43.2, P = .045) and average flap initiation attempts (16.1 vs 23.3, P = .042). Surgical efficiency was better for attendings (45% vs 37% of approaches led to case progression, P = .038). There was no significant difference between groups in total flap extension attempts or intrasurgical complications. Conclusions: Compared to fellows, attendings peel ILM in MH surgery faster, more efficiently with a lower number of flap initiation attempts and total movements.